A Novel Soybean Intrinsic Protein Gene, GmTIP2;3, Involved in Responding to Osmotic Stress - Zhang, Dayong; Tong, Jinfeng; He, Xiaolan; Xu, Zhaolong; Xu, Ling; Wei, Peipei; Huang, Yihong; Brestic, Marian; Ma, Hongxiang; Shao, Hongbo (Frontiers in Plant Science, 2016)
Water is essential for plant growth and development. Water deficiency leads to loss of yield and decreased crop quality. To understand water transport mechanisms in plants, we cloned and characterized a novel tonoplast intrinsic protein (TIP) gene from soybean with the highest similarity to TIP2-type from other plants, and thus designated GmTIP2;3. The protein sequence contains two conserved NPA motifs and six transmembrane domains. The expression analysis indicated that this gene was constitutively expressed in all detected tissues, with higher levels in the root, stem and pod, and the accumulation of GmTIP2;3 transcript showed a significant response to osmotic stresses, including 20% PEG6000 (polyethylene glycol) and 100 μM ABA (abscisic acid) treatments. The promoter-GUS (glucuronidase) activity analysis suggested that GmTIP2;3 was also expressed in the root, stem, and leaf, and preferentially expressed in the stele of root and stem, and the core promoter region was 1000 bp in length, located upstream of the ATG start codon. The GUS tissue and induced expression observations were consistent with the findings in soybean. In addition, subcellular localization showed that GmTIP2;3 was a plasma membrane-localized protein. Yeast heterologous expression revealed that GmTIP2;3 could improve tolerance to osmotic stress in yeast cells. Integrating these results, GmTIP2;3 might play an important role in response to osmotic stress in plants.